Ceritinib and cabozantinib: new tyrosine kinase inhibitors improve treatment options for non-small cell lung cancer patients - Viteri, Santiago; Rosell, Rafael (Translational Cancer Research, 2017)
In The Lancet, Jean Charles Soria and colleagues presented the results of the ASCEND-4 study: a randomized phase 3 trial comparing ceritinib against platinum doublet chemotherapy as first line treatment for non-small cell lung cancer (NSCLC) patients harboring anaplastic lymphoma kinase (ALK) rearrangements that included 376 patients (189 in the ceritinib arm and 187 in the chemotherapy arm) (1).